Dampak Pemimpin Etis, Efektivitas Pemimpin, dan Stress Kerja terhadap Niat Berpindah Karyawan - Egal Radhika Maulana; Bambang Nur Cahyaningrum; Ariyani Wahyu Wijayanti (Journal Of Business, Finance, and Economics (JBFE), 2020)
The purpose of this study is to examine and analyze the impact of ethical leaders, leader effectiveness, and work stress on the intention to move employees of CV Rimba Sentosa Tawangsari. The sample in this study was 115 employees of CV Rimba Sentosa Tawangsari. The sampling method used is nonprobability sampling, while the sampling technique used is convenience sampling. Testing the hypothesis in this study using SEM (Structural Equation Modeling) analysis. The results of this study, showed that the ethical leader variable and the effectiveness of the leader, had no effect on work stress. The variable of ethical leader and work stress, does not affect employee intention to move. The leader effectiveness variable has a significant effect on employee turnover intentions. Keywords: Ethical leader, leader effectiveness, work stress, employee turnover intentions